131k views
2 votes
Solve the system by elimination

-2x + 2y + 3z = 0
-2x - y + z = -3
2x + 3y + 3z = 5

User Sevle
by
4.6k points

1 Answer

6 votes

In point form, (1, 1, 0), or equation form:


x=1,y=1,z=0

_________________________________________________

How So?

Well,....

Isolate x for -2x + 2y + 3z = 0:


x=(2y+3z)/(2)

Substitute
x=(2y+3z)/(2):


[-2*(2y+3z)/(2)-y+z=-3; 2*(2y+3z)/(2)+3y+3z=5]

Simplify:


[-3y-2z=-3; 5y+6z=5]

Isolate y for -3y - 2z = -3:


y=-(-3+2z)/(3)

Substitute y = - -3+2z/3:


[5(-(-3+2z)/(3))+6z=5

Simplify:


[(15+8z)/(3)=5]

Isolate z for [15+8z/3 = 5]:

For y = - -3+2z/3

Substitute z = 0


y=-(-3+2 * 0)/(3)
=1


y=1

For x = 2y+3z/2

Substitute z = 0, y = 1


x =(2*1+3*0)/(2)

Simplify:


x = 1

Hence, the solutions to the system of equations are:


x = 1, y=1, z=0

Hope this helps!

User Adar Hefer
by
5.0k points